2012
DOI: 10.1371/journal.pone.0039967
|View full text |Cite
|
Sign up to set email alerts
|

DOK3 Negatively Regulates LPS Responses and Endotoxin Tolerance

Abstract: Innate immune activation via Toll-like receptors (TLRs), although critical for host defense against infection, must be regulated to prevent sustained cell activation that can lead to cell death. Cells repeatedly stimulated with lipopolysaccharide (LPS) develop endotoxin tolerance making the cells hypo-responsive to additional TLR stimulation. We show here that DOK3 is a negative regulator of TLR signaling by limiting LPS-induced ERK activation and cytokine responses in macrophages. LPS induces ubiquitin-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 37 publications
(60 reference statements)
2
30
2
Order By: Relevance
“…In contrast, we demonstrate here a positive role for DOK3 in the induction of IFN-b production during virus infection and poly(I:C) stimulation of macrophages. We observed that DOK3 did not undergo degradation upon poly(I:C) stimulation, consistent with previous findings (12). Its presence facilitates TBK1 and TRAF3 interaction during virus infection and likely enables maximal transduction of downstream signaling for optimal IFN-b production.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In contrast, we demonstrate here a positive role for DOK3 in the induction of IFN-b production during virus infection and poly(I:C) stimulation of macrophages. We observed that DOK3 did not undergo degradation upon poly(I:C) stimulation, consistent with previous findings (12). Its presence facilitates TBK1 and TRAF3 interaction during virus infection and likely enables maximal transduction of downstream signaling for optimal IFN-b production.…”
Section: Discussionsupporting
confidence: 91%
“…This is in contrast to the demonstrated degradation of DOK1-3 proteins in LPS-stimulated macrophages (12), suggesting that DOK3 could have a different role in TLR3 activation in macrophages. In this study, we examined the involvement of DOK3 in TLR3 signaling and showed that the adaptor was phosphorylated upon poly(I:C) stimulation and played a critical role in TLR3-triggered IFN-b production.…”
contrasting
confidence: 79%
See 2 more Smart Citations
“…Suppressor of cytokine signaling (SOCS) proteins are important negative regulators of the TLR signaling pathway, and have been shown to play a role in the induction of tolerance in macrophages (28,29). The expression of suppressor of cytokine signaling 1 was measured in LPS-tolerized AECs, and was found to significantly increase after secondary LPS ( Figure 5A).…”
Section: Negative Tlr Regulators Do Not Mediate Tolerance In Aecsmentioning
confidence: 99%